The Efforts of Islamic Religious Education Teachers to Foster Students’ Religious Character through Religious Extracurricular Practices in Schools - Junaedi; Ahmad Sukandar (Journal of Science and Education (JSE), 2025)
This study examines the efforts of Islamic Religious Education (PAI) teachers in fostering students’ religious character through religious extracurricular practices in two high schools with different contexts: SMA Karya Pembangunan 2 (general school) and SMA Muhammadiyah 4 (faith-based school) in Bandung City. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis, involving PAI teachers, extracurricular advisors, and active student participants. The findings reveal that SMA Karya Pembangunan 2 adopts a contextual and inclusive approach, integrating religious values with contemporary social issues and promoting tolerance through activities such as interfaith seminars. This model enhances students’ moral reasoning, empathy, and respect for diversity. In contrast, SMA Muhammadiyah 4 emphasizes structured habituation, including daily muhasabah, peer mentoring, and a tahfidz program requiring one juz memorization per year. This approach cultivates discipline, responsibility, and consistency in religious practice.Key supporting factors include stakeholder collaboration, notably in SMA Muhammadiyah 4 through home visit programs involving teachers, parents, and community members. The main challenge in SMA Karya Pembangunan 2 is the variation in students’ religious understanding, requiring differentiated instructional strategies. The study concludes that combining inclusivity with spiritual depth can offer a holistic framework for religious character development, aligning with the Penguatan Pendidikan Karakter (PPK) initiative.